FACTORS THAT INFLUENCE THE PRICE EARNING RATIO (PER) ON COMPANIES LISTED ON LQ45 INDEX INTHE YEAR 2010-2013 - B11111047, Dewi (Jurnal Manajemen Update, 2015)
One of the fundamental analyses that is often used by investors and securities analysts in assessing the stock price is the price earning ratio (PER). The price earning ratio shows how much investors are willing to pay for each of the company’s profit. This study aimed to examine the influence of debttoequity ratio (DER), price to book value (PBV), return on assets (ROA), and return on equity (ROE) on the price earning ratio (PER). The samples of the research were 23 companies listed on LQ45 index. The data used was secondary data from each company listed on LQ45 index for the period of 4 years i.e. 2010, 2011, 2012 and 2013. The samples werechosenthrough   purposive   sampling.   The   data   analysis   usedthe   multiple regression test preceded by the classic assumption test consisting of normality test, multicollinearity test, autocorrelation and heteroscedasticity test. The hypothesis testing was conducted by using the f-test and t-test. The results of the research showed that the variable of the debt equity ratio (DER) and the return on equity (ROE) had a negative influence on the price earning ratio (PER);the price to book value (PBV) had a positive influence on the price earning ratio (PER), while the return on assets (ROA) had no influence on the price earning ratio (PER) of shareson LQ45 index. Keywords: Debt Equity Ratio (DER), Price Book Value (PBV), Return on Assets   (ROA), Return on Equity (ROE), Price Earning Ratio (PER).